Unity and Closure through Performatism: A Possible Replacement of Postmodernism? - Ammar, Ali; Ahmad, Munawar Iqbal (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2022)
Through the use of aesthetically mediated devices, the contemporary literary theory is argued, by Raoul Eshelman, to have ushered into a new epoch-making era of performatism by assigning unity and closure to the current art works in the world. Eshelman attempts to apply his newly formed concept in different art works ranging from literary writings to architecture, movies and paintings in his book, Performatism or End of Postmodernism in 2008. This paper is an attempt to overview and analyse the concept of Performatism by applying it, as an example, on a recent Pakistani narrative The Party Worker by Mohsin Hamid Shahid. The rationale for the selection of this work is owing to the claim by Eshelman that Performatism has seeped into art works globally. The textual analysis of the selected novel signifies that Eshelman’s view of contemporary state of literary theory cannot be neglected as there are attempts at unification and closure of the narratives, a departure from postmodern disintegration and fragmentation. However, the imposition of unity and closure owing a great deal to the use of aesthetic devices and authoriality through the strategic maneuvering by the writer poses a threat to the smooth shifting from postmodernism to performatism.